Adding Robustness to Libyan National Identification Number (LNIN) System - Beraam, Abdulraheem A.; El-Lhweje, Lutfi S. (The Libyan Journal of Science, 2022)
Errors can be introduced into data through a variety of means. Libyan National Identification Number (LNIN) which lately has been introduced and became the source of identifying Libyan citizen is no exception. However, the LNIN was constructed without any base for validation. The other vulnerability is the weak authentication process when individuals inquire their LNIN especially via web site. One can increase reliability by introducing check digits to the right end of the LNIN. Check digit is generally designed to detect and to capture human transcription errors and to protect against corruption in the number itself (i.e., a single mistyped digit or some permutations of two successive digits). The introduction of check digits does not mean secrecy. Our goal is twofold; review the concept and the benefit of check digit, where several well known algorithms will be presented and propose a strategy to smoothly fix the LNIN by adapting an algorithm which satisfies the requirements of the LNIN, and strengthen the authentication process before revealing sensitive information via web site.